Good Corporate Governance and Financial Performance of Pharmaceutical Companies in Indonesia - Karnila Ramadhani Tuharea; Mursalam Salim; Marten Puyo (ACCOUNTABILITY, 2024)
Good Corporate Governance is a fundamental factor in producing reliable financial performance, so it will influence investors' judgment in determining their investments. This research aims to examine the influence of Good Corporate Governance as proxied by the Board of Directors, Board of Commissioners, and Audit Committee on the company's Financial Performance (Return On Assets). This research is archival research using annual report data from pharmaceutical companies listed on the Indonesia Stock Exchange. The data processed is data from the Board of Directors, Board of Commissioners, Audit Committee, and Financial Performance (Return On Assets). The population used in this research was 12 pharmaceutical companies during the 2018-2022 period with samples obtained from 8 companies using purposive sampling techniques. This research uses multiple regression analysis as a data analysis method with tools Eviews Software 12. The results of this research conclude that the Board of Commissioners, Board of Directors, and Audit Committee influence financial performance, while the Independent Board of Commissioners does not influence financial performance.